The Influence of Internal Audit on The Quality of Financial Statements - Ayi Astuti (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2022)
This research aim to know influence of assessment of internal audit performance to internal control system, influence of applying of internal audit to internal control system, and influence of assessment of performance and applying of internal audit both of internal control system. The research has been done by questionnaires internal auditor. The respondent are auditor’s who worked in company of bankings residing in Bandung 45 responders. To analyze data researcher used SPSS 20 Version. Partially, internal audit performance and internal audit applying variable have influence significance of internal control system.